2021
DOI: 10.1177/02601060211032886
|View full text |Cite
|
Sign up to set email alerts
|

Examining correlates of feeding practices among parents of preschoolers

Abstract: Background: Parent feeding practices play a critical role in children’s eating behaviors. Limited research has explored child-level correlates of parent feeding practices. Aim: To identify correlates of feeding practices (responsive and controlling) among parents of preschoolers US. Methods: Participants included parents (n = 273) of preschoolers (3–5 years), recruited from Early Care and Education settings (n = 24) located in a metropolitan city in the US. Analysis included descriptives, correlations, and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Characteristics of the included studies are shown in Table 1 . The studies were published between 2001 and 2022, conducted in the US ( n = 12) [ 21 , 24 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], Australia ( n = 6) [ 26 , 27 , 75 , 76 , 77 , 78 ], Brazil ( n = 4) [ 28 , 30 , 50 , 79 ], Sweden ( n = 4) [ 22 , 80 , 81 , 82 ], China ( n = 2) [ 83 , 84 ], the Netherlands ( n = 1) [ 85 ], Ethiopia ( n = 1) [ 29 ], the UK ( n = 1) [ 86 ], Mexico ( n = 1) [ 87 ], South Korea ( n = 1) [ 88 ], Portugal ( n = 1) [ 23 ], India ( n = 1) [ 25 ], and France ( n = 1) [ 74 ]. The study designs were a cross-sectional study ( n = 32) and a cohort study ( n = 3) [ 23 , 26 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Characteristics of the included studies are shown in Table 1 . The studies were published between 2001 and 2022, conducted in the US ( n = 12) [ 21 , 24 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], Australia ( n = 6) [ 26 , 27 , 75 , 76 , 77 , 78 ], Brazil ( n = 4) [ 28 , 30 , 50 , 79 ], Sweden ( n = 4) [ 22 , 80 , 81 , 82 ], China ( n = 2) [ 83 , 84 ], the Netherlands ( n = 1) [ 85 ], Ethiopia ( n = 1) [ 29 ], the UK ( n = 1) [ 86 ], Mexico ( n = 1) [ 87 ], South Korea ( n = 1) [ 88 ], Portugal ( n = 1) [ 23 ], India ( n = 1) [ 25 ], and France ( n = 1) [ 74 ]. The study designs were a cross-sectional study ( n = 32) and a cohort study ( n = 3) [ 23 , 26 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“… Effects of concern about child overweight on restrictive feeding (evaluated using β ) [ 21 , 22 , 23 , 26 , 27 , 29 , 74 , 76 , 83 , 84 , 85 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations